2016
DOI: 10.18404/ijemst.61149
|View full text |Cite
|
Sign up to set email alerts
|

STEMulating Interest: A Meta-Analysis of the Effects of Out-of-School Time on Student STEM Interest

Abstract: This study is a meta-analysis of the effects of out-of-school time (after school, summer camps, enrichment programs, etc.) on the student interest in STEM. This study was guided by the following research questions: (1) How effective is OST as a means to foster student interest in STEM? (2) How does the effectiveness of OST differ by program and study characteristics? A total of 19 independents effect sizes were extracted from 15 studies investigating the effect of out-of-school time (OST) on STEM interest. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 60 publications
6
86
0
4
Order By: Relevance
“…Students who participate in expanded learning opportunities are also 20% less likely to drop out of school and 30% less likely to participate in criminal activities than peers who did not participate (Moeller & Reitzes, 2011;Vandell, Reisner, & Pierce, 2007). While studies among middle and high school students often demonstrate significant positive effects of out-of-school time (OST) STEM programs on youth interest in STEM, data about how similar programs impact elementary students' interest in STEM are lacking (Young, Ortiz, & Young, 2017). Existing after-school programs that provide such opportunities to youth can utilize various pedagogical methods, such as inquiry-based learning (IBL), project-based learning, and peer-led team learning (Alexander, 2000).…”
Section: A Critical Time For Stem Education In After-school Timementioning
confidence: 99%
“…Students who participate in expanded learning opportunities are also 20% less likely to drop out of school and 30% less likely to participate in criminal activities than peers who did not participate (Moeller & Reitzes, 2011;Vandell, Reisner, & Pierce, 2007). While studies among middle and high school students often demonstrate significant positive effects of out-of-school time (OST) STEM programs on youth interest in STEM, data about how similar programs impact elementary students' interest in STEM are lacking (Young, Ortiz, & Young, 2017). Existing after-school programs that provide such opportunities to youth can utilize various pedagogical methods, such as inquiry-based learning (IBL), project-based learning, and peer-led team learning (Alexander, 2000).…”
Section: A Critical Time For Stem Education In After-school Timementioning
confidence: 99%
“…The number of American students earning bachelor's degrees increased by 16% over the past 10 years, however, the number of bachelor's degrees earned in engineering decreased by 15% (O'Riley, 2013). Nationally, less than 50% of the students who enrolled in engineering curriculum complete the program (Young, Ortiz & Young, 2017). American Universities typically lose 50% or more of engineering freshmen and sophomore during the first two years of their engineering program.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, low confidence and selfefficacy in STEM subjects form as early as grade six (Heaverlo et al, 2013). Early intervention to mitigate negative influences can ultimately have an effect on a women's choice to enter STEM (Young, Ortiz, & Young 2017;Bieri Buschor, Berweber, Keck Frei, & Kappler, 2014;Hughes, 2015;Wang & Degol, 2013;Heaverlo et al, 2013).…”
Section: Middle School As An Important Time For Interventionmentioning
confidence: 99%
“…Most middle school programming aims to build interest in STEM, which can become a factor in decisions about college major and career path (Hall, Dickerson, Batts, Kauffmann & Bosse, 2011;Tsui, 2009). From a meta-analysis of 15 studies of out-of-school time STEM programs at the elementary, middle school, and high school levels, Young, Ortiz, and Young (2017) concluded that out-of-school time has a positive effect on student interest in STEM at the middle school and high school level, regardless of student gender. Additionally, middle school intervention programs can have a positive effect on STEM identity, help mitigate negative peer pressure, and neutralize adverse influences such as stereotype threat (Hughes, 2015;Wang & Degol, 2013).…”
Section: The Efficacy Of Stem Outreach Programs For Middle School Girlsmentioning
confidence: 99%
See 1 more Smart Citation